Knowledge, Attitude and Practice of HIV/AIDS Voluntary Counseling and Testing and Quality of VCT Services among the Students of Kassala and Kordofan Universities, Sudan (2014 -2016) - E. Ahmed, Magda; A. O. Mohammed, Musa (Gezira Journal of Health Sciences, 2017)
Many countries have been trying to take many different approaches in an attempt to slow the spread of HIV infection and minimize its impact on the individual, family and society.These strategies include voluntary counseling and testing (VCT).A cross sectional study was conducted to study the Knowledge, Attitude and Practice of voluntary HIV/AIDS counseling and testing services (VCT) among students of Kassala and KordofanUniversities and Quality of VCT Services in Kassala and Elobied cities, Sudan. Building on foundations (universities). A total of (384) students of Kassala and Kordofan Universities,who were selected through a stratified sampling method, filled a self-administered questionnaire. Data was analyzed using the Statistical Package of Social Sciences (SPSS) version (11.5) software and chi-square test was used to determine an association between a number of independent and dependent variables. Self-administered questionnaires having closed questions were also distributed to counselors, lab technicians and nurses to assess quality of VCT services delivery from them.The findings showed that most of the participants (95.9%) had known HIV/AIDS. (96.2%) who knew HIV/AIDS transmission method. most of the students (89.5%) knew VCT services. A few of students (21.6%) dealing with people living with HIV/AIDS. Majority of participants (92.4%) had dealt with people living with HIV/AIDS.Most of students (76.5%) have not had VCT. Fears of (a positive test result, stigma and discrimination) were the main barriers for VCT utilization from (94.3%) of universities students. Most of students (90%) of VCT centers have had counseling rooms. More tertian of VCT providers (72.4%) were obtained on verbal consent. (87.8%) of VCT providers had received training in VCT.There was a significant association between utilization of VCT and social stigma (PV= 0.003, df = 1, χ2 = 8.878).Therewas a significant association between knowledge regarding VCT center services and utilization of VCT cervices (PV= 0.014, df = 1, χ2 = 6.068). The study recommended to activate the role of VCT centers awareness should be raised among students in order to promote the utilization of VCT services. Reduce the social stigma towards utilization of VCT centers.